FDI and Economic Growth Relationship Based on Cross-Country Comparison - Gursoy, Faruk; Sekreter, Ahmet; Kalyoncu, Huseyin (International Journal of Economics and Financial Issues, 2013)
This paper aims to investigate empirically the impact of FDI on economic growth for Azerbaijan, Kyrgyz Republic, Kazakhstan, Tajikistan, Turkmenistan, and Uzbekistan over the period 1997-2010. The Johansen cointegration and Granger causality tests are used in order to analyze the causal relationship between FDI and economic growth. It is crucial to see the directions of causality between two variables for the policy makers to encourage private sectors. The cointegration test results indicated that FDI and Economic Growth variables are cointegrated for Azerbaijan and Turkmenistan. By using Granger Causality test we found that FDI causes GDP for Azerbaijan and bidirectional causality is observed for Turkmenistan. Keywords: Economic growth; foreign direct investment; Granger causality JEL Classifications: C32; F21; O4